Time and Cost Performance Evaluation Using Earned Value Management in Residential Construction Projects: A Case Study of the Hanglekir Housing Development - Riris Setiyowati; Jalaludin Jalaludin (Asosiasi Dosen Muda Indonesia, 2026)
Construction projects frequently experience discrepancies between planned schedules and actual implementation, resulting in delays and cost inefficiencies. Therefore, effective monitoring is needed to evaluate project performance and maintain alignment with planned time and budget targets. Objective: This study evaluates the time and cost performance of the Hanglekir Residential Housing Development Project using the Earned Value Management (EVM) approach. Methodology: This research employed a mixed-method case study design. Quantitative data were obtained from project documents, including cost budget plans, schedules, and progress reports, while qualitative data were collected through field observations and interviews. Project performance was analyzed using EVM indicators, namely Schedule Variance (SV), Cost Variance (CV), Schedule Performance Index (SPI), Cost Performance Index (CPI), and forecasting indicators such as Estimate at Completion (EAC) and Estimate at Schedule (EAS). Findings: The results indicate that the project experienced schedule delays, as shown by SPI values consistently below 1. However, cost performance was relatively efficient in several periods, reflected by CPI values above 1. Forecasting results show that the final project cost is likely to remain below the initial budget, while the completion time is expected to slightly exceed the planned schedule. Implications: These findings demonstrate the importance of integrated project monitoring to improve time and cost control. Originality: This study provides empirical evidence of the practical application of EVM for evaluating both schedule and cost performance in a residential construction project.